2018
DOI: 10.1016/j.molmet.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimal housing temperatures for mice to mimic the thermal environment of humans: An experimental study

Abstract: ObjectivesThe laboratory mouse is presently the most common model for examining mechanisms of human physiology and disease. Housing temperatures can have a large impact on the outcome of such experiments and on their translatability to the human situation. Humans usually create for themselves a thermoneutral environment without cold stress, while laboratory mice under standard conditions (≈20° C) are under constant cold stress. In a well-cited, theoretical paper by Speakman and Keijer in Molecular Metabolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
207
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(234 citation statements)
references
References 34 publications
16
207
4
Order By: Relevance
“…An interesting counter argument based on the metabolic rate range and increase below the thermoneutral region suggested that singly housed mice at 23-25°C was an appropriate model for humans [41]. A response noted that metabolic rate in a mouse at thermoneutrality ranged 1.8-fold above the BMR [42].…”
Section: Thermal Physiology In Small Mammals Is About Keeping Warmmentioning
confidence: 99%
“…An interesting counter argument based on the metabolic rate range and increase below the thermoneutral region suggested that singly housed mice at 23-25°C was an appropriate model for humans [41]. A response noted that metabolic rate in a mouse at thermoneutrality ranged 1.8-fold above the BMR [42].…”
Section: Thermal Physiology In Small Mammals Is About Keeping Warmmentioning
confidence: 99%
“…Additionally, there was reduced diurnal rhythmicity in the RER of both WT and Fgf13 +/2 animals housed at 30°C compared with 22°C housing, which has been previously observed in ref. 43. We hypothesized that the increased utilization of fat as a fuel source was due to altered behavior of the Fgf13 +/2 mice during the measurement period in metabolic cages compared with standard thermoneutral housing, possibly because of the necessity of housing the animals singly in the metabolic cages.…”
Section: Fgf13 +/2 Mice Exhibit Hyperactivity When Housed At 22°c Andmentioning
confidence: 99%
“…Most studies are conducted with cold-stressed mice due to the unique physiology of mice. This is an important variable of mouse physiology that should be considered in all studies trying to model human health and disease (44)(45)(46). The tamoxifen-inducible systemic knockout Nf1 adult model is an example where room temperature versus thermoneutral conditions alters the phenotype in an unexpected way.…”
Section: Discussionmentioning
confidence: 99%